BS37 Leukocytic nitrate reductase activity mitigates systemic inflammation-induced endothelial dysfunction in humans by accelerating resolution. (6th June 2022) - Shabbir, Asad; Rathod, Krishnaraj; Primus, Chris; Lau, Clement; Chhetri, Ismita; Ono, Mutsumi; Khambata, Rayomand; Massimo, Gianmichele; Kapil, Vikas; Ahluwalia, Amrita
Abstract : Introduction: Inflammation is implicated in endothelial dysfunction in CVD. A key mechanism mediating endothelial dysfunction is a reduction in bioavailable (eNOS-derived) nitric oxide (NO). Evidence has shown that increasing NO delivery via activation of the non-canonical pathway might increase anti-inflammatory and vascular protective NO. We hypothesise that inorganic nitrate (NO3-) will increase bioavailable NO and attenuate the inflammatory pathways leading to endothelial dysfunction in healthy volunteers. To identify mechanisms in the immune response we have undertaken 2 prospective double-blind RCTs: Blister-NITRATE (NCT0318383) and Typhoid-NITRATE (NCT02715635 ). Methods: Blister-NITRATE; using a cantharidin-induced skin blister model, 24hr and 72hr blisters were harvested pre- and post- 8 days of 8–12mmol of nitrate or placebo. Blister exudate was analysed for leucocyte activation state (CD11b, CD62L, CD162) using flow cytometry and for cytokines/chemokines (n=36). Typhoid-NITRATE; using a model of typhoid vaccine-induced systemic inflammation, flow-mediated dilatation (FMD) and GTN-induced brachial artery dilatation were measured pre- and post- 6 days of 8–12mmol of nitrate or placebo. Blood was collected 8hr after vaccination for flow cytometry, using the same markers (n=78). Blood, urine, and saliva were collected for nitrite (NO2-) and NO3- quantification. Results: Dietary nitrate increases plasma, urine, and saliva [NO2-] and[NO3-], indicating intact activation of the non-canonical pathway. FMD was preserved in the group treated with dietary nitrate, compared with placebo (absolute reduction1.4%±1.6%, P<0.0001), with no difference in GTN-induced brachial artery dilatation (P=0.931) (figure 1). A decreased systemic proportion of intermediate monocytes (P=0.0034) and CD62L expression (P=0.0112) was identified. In nitrate treated volunteers, a significantly increased expression of CD11b CD3+/CD4+ T-cells was evident (P=0.0159), with a pro-resolution phenotype comprised of increased anti-inflammatory TGFβ (P=0.04) and IL-35 (P=0.04) and blunting of pro-inflammatory IFNγ and MCP-1/CCL2 (figure 2). Skin blisters resolved more rapidly in volunteers treated with dietary nitrate (P=0.0425), with reduced neutrophils (P=0.017), intermediate monocytes (P=0.001) and expression of inflammatory (CD11b P=0.03, CD162 P=0.05, CD62L P=0.053) and intermediate monocytes (CD11b P=0.01, CD62L P=0.03) surface markers at 72hrs. Conclusions: Inorganic nitrate suppresses endothelium-mediated vascular dysfunction. Dietary nitrate influences the localised and systemic inflammatory response through suppressing of pro-inflammatory cell types with reduced inflammatory and intermediate monocytes, and attenuated inflammatory cytokines and chemokines. The intervention induces a pro-resolution phenotype. Inorganic dietary nitrate influences endothelial function through the modulation of inflammatory responses and might be of potential therapeutic benefit in patients with established CAD.